Evaluation of the ability of powdered milk to produce minitablets containing paracetamol for the paediatric population - Pinto, Joana T. (2017)
The work aims at evaluating the usefulness of powdered milk as a drug matrix for the production of minitablets specifically designed for children. Mixtures made of powdered milk, paracetamol, mannitol, sodium croscarmellose and magnesium stearate (evaluated for flow properties, cohesiveness and caking tendency) were compacted into beams (evaluated for deformation, elasticity and stiffness) and minitablets (evaluated for uniformity of mass, thickness, tensile strength and paracetamol mean dissolution time) and a 23 factorial design performed. The increase on milk fraction in the formulation improved the compressibility of paracetamol and hardness of compacts, reducing weight variation and paracetamol release. A marked decrease on the dissolution time was observed as sodium croscarmellose was added to the milk rich formulations. The increase of the compression force resulted in the production of thinner compacts but had little effect on dissolution time. The production of beams has shown that deformation, bending strength and stiffness increased with both milk and compaction pressure, and decreased with sodium croscarmellose, whereas elasticity decreased when all variables increased. Tensile strength and mean dissolution time described minitablets well, unlike compaction force. The study has proved that powdered milk is suitable for the production of minitablets by direct compression of poor compressible drugs.